Removal of Celestine Blue Dye From Textile Wastewater by Adsorption over the Mixed Oxide NiO –MgO - Huda Salam Ghani (Journal of Global Pharma Technology, 2017)
This study was carried out for the purpose of estimating the adsorption kinetics and removal of Celestine Blue Dye from textile wastewater by adsorption over mixed oxides NiO–MgO that prepared in our laboratory. The optimum conditions for removal  were studied which includes the appropriate concentration of dye as well as weight of adsorbent, temperature ,pH effect, speed of shaking  and optimum time for the removal  where the best concentration of the adsorption process is ( 100 ppm), the best economic weight is( 0.025 gm)at( 45 min) shaking time at the acidity of the dye which is( pH = 5) and shaking speed of( 175 cycle per minute) at the temperature of the laboratory (25oC ).Keywords: Adsorption, Mixed oxides, Celestine blue B dye.